Accuracy of medication labels on community pharmacy-prepared dose administration aids: An observational study - Zulal Uzunbay; Rohan A. Elliott; Simone Taylor; Daniela Sepe; Emily J. Ferraro (Elsevier, 2023)
Background: Hospital prescribers often use the labels on multicompartment compliance aids or monitored dosage systems, known in Australia as dose administration aids (DAAs), as a trusted source of information about patients' medication regimens taken in the community. Aim: The primary aim was to explore the prevalence and nature of labelling incidents on community pharmacy-prepared DAAs. Methods: A convenience sample of 100 adult patients admitted to a metropolitan teaching hospital who used a community pharmacy-prepared DAA at home was recruited. Patients were excluded if their DAAs were not brought to hospital. As part of usual care, a pharmacist took a best possible medication history (BPMH) using multiple information sources. This 'gold standard' BPMH was compared to the regimen listed on the DAA summary label and the DAA contents. The primary outcome was the percentage of patients whose DAA summary label(s) had one or more incidents for DAA packed medications. DAA label incident was defined as incorrect, missing or illegible/ambiguous medication name, strength, dose or dose-form when compared to the BPMH and DAA contents. Secondary outcomes were compliance with best-practice guidelines for labelling DAAs; and percentage of patients with a DAA packing error. Results: The 100 patients used 110 DAAs, packed by 75 community pharmacies. Four (4.0%) patients had no medication summary label on their DAAs. Of the 96 patients whose DAA(s) had a summary label, 82 (85.4%) had one or more summary label incidents. The most prevalent incidents were 'illegible, ambiguous or missing medication details', 'truncated medication name' and 'omission of a medication'. The most prevalent guideline non-compliance was not including generic medication names (68% DAA-packed medications). Two DAA packing errors were identified. Conclusion: A high prevalence of DAA labelling incidents was identified. Improved DAA labelling software functionality, more robust pharmacy procedures and pharmacy staff education are required.